Threelobe morningglory (Ipomoea triloba) germination and response to herbicides - Chauhan, Bhagirath Singh; Abugho, Seth Bernard (Cambridge University Press, 2012)
Experiments were conducted in the laboratory and screenhouse to determine the effects of scarification; alternating day/night temperatures; light, salt, and water stress; seed burial depth; and rice residue on seed germination and seedling emergence of threelobe morningglory, and to evaluate the response of this weed to commonly available POST herbicides in the Philippines. Germination was stimulated by seed scarification, suggesting that inhibition of germination in this species is mainly due to the hard seed coat. Germination of the scarified seeds was not influenced by the tested temperatures (alternating day/night temperatures of 25/15, 30/20, and 35/25 C) and light. The concentrations of sodium chloride, ranging from 0 to 250 mM, did not influence germination of the scarified seeds of threelobe morningglory. The osmotic potential required for 50% inhibition of maximum germination was −0.35 MPa, although some seeds germinated at −0.6 MPa. Seedling emergence was greatest for the seeds placed on the soil surface (96%), and emergence declined with increased burial depth in soil. The burial depth required for 50% inhibition of maximum emergence was 2.8 cm. No seedlings emerged from a burial depth of 6 cm or greater. Residues of up to 6 Mg ha−1on the soil surface did not influence seedling emergence of threelobe morningglory. The herbicide 2,4-D at 400 g ai ha−1provided excellent control of threelobe morningglory when applied at the four-leaf (100%) and six-leaf (97%) stages. However, at the eight-leaf stage, percent control was reduced to 67% and herbicide rate had to be increased twofold to achieve 95% control. The information gained from this study could contribute to developing components of integrated weed management strategies for threelobe morningglory. Soil inversion by tillage to bury weed seeds below their maximum depth of emergence and early application of an effective POST herbicide could serve as important tools for managing threelobe morningglory.